2013
DOI: 10.1002/cphc.201200822
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Molecular Design for Supramolecular Network Engineering on a Silicon Surface

Abstract: An open‐and‐shut case: By using tailored molecules, the formation of open or close‐packed supramolecular network can be achieved on a silicon‐based surface. The role of molecule–molecule interactions and molecule–substrate interactions to control the geometry of organic network on semi‐conductor surface is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 45 publications
7
31
0
Order By: Relevance
“…This qualitative behavior has already been reported for the similar molecule TIPB. 48 The protrusions associated with the iodine atoms do not have the 3-fold symmetry expected for TIPT molecules. We ascribe this to an electronic effect.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…This qualitative behavior has already been reported for the similar molecule TIPB. 48 The protrusions associated with the iodine atoms do not have the 3-fold symmetry expected for TIPT molecules. We ascribe this to an electronic effect.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Our work in this domain illustrates well the effect of temperature in self-assembly formation [22][23][24]. Although molecular deposition Reprinted with permission from [19] was performed at room temperature, this thermal energy was sufficient for molecules to overcome diffusion barriers and then form different self-assemblies.…”
Section: Heatmentioning
confidence: 90%
“…Recently, we have demonstrated that the molecule-surface interactions can be controlled by using the Si(111)-B-(√3 × √3)-R30°surface, noted Si(111)-B. The silicon adatoms dangling bonds are depopulated because of the presence of a boron atom underneath each silicon adatom, leading to a weak π-conjugated moleculesurface interaction [22,24,[50][51][52]. In all these cases, molecule-surface interaction is weak enough to achieve the formation of large-scale supramolecular networks.…”
Section: Adsorption Of Bistable Azobenzene Molecules On Semiconductorsmentioning
confidence: 99%
“…Supramolecular networks on a doped boron silicon surface under ultra high vacuum (UHV) have been recently obtained (Makoudi et al, 2013). The used molecule contains different end-groups, bearing either bromine, iodine or hydrogen atoms denoted 1,3,5-tri(4 -bromophenyl)benzene (TBB), 1,3,5-tri(4-iodophenyl)benzene (TIB) and 1,3,5-triphenyl-benzene (THB).…”
Section: Introductionmentioning
confidence: 99%